2015
DOI: 10.1017/jfm.2015.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of finite sampling time on estimation of Brownian fluctuation

Abstract: We present a study of the effect of finite detector integration/exposure time E, in relation to interrogation time interval t, on analysis of Brownian motion of small particles using numerical simulation of the Langevin equation for both free diffusion and hindered diffusion near a solid wall. The simulation result for free diffusion recovers the known scaling law for the dependence of estimated diffusion coefficient on E/ t, i.e. for 0 E/ t 1 the estimated diffusion coefficient scales linearly as 1 − (E/ t)/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…MTV data can also experience a temporal filtering effect associated with the averaging that occurs over the exposure period of the ICCD. This effect is physically similar to that found by Pouya et al (2015) in the context of experimentally estimating the intensity of Brownian fluctuations with finite sampling time sensors. In this regard, there are trade-offs associated with the camera time delay and exposure duration relative to accurately measuring the u ′ profiles.…”
Section: Mean and Rms Streamwise Velocitysupporting
confidence: 86%
“…MTV data can also experience a temporal filtering effect associated with the averaging that occurs over the exposure period of the ICCD. This effect is physically similar to that found by Pouya et al (2015) in the context of experimentally estimating the intensity of Brownian fluctuations with finite sampling time sensors. In this regard, there are trade-offs associated with the camera time delay and exposure duration relative to accurately measuring the u ′ profiles.…”
Section: Mean and Rms Streamwise Velocitysupporting
confidence: 86%
“…Because the height of the microstructures fabricated by using T-NIL was less than 500 nm, MnPIV can therefore be applied in 3D flow measurements around these microstructures. We examined the hindrance factor for Brownian motion normal to the glass plate using the TIRFM (Pouya et al 2015), which is approximated by the following equation (Bevan and Prieve 2000):…”
Section: Mnpiv With Microstructures Fabricated From Mexflon By Using mentioning
confidence: 99%
“…Recently, we conducted simulations of single particle tracking in a nanochannel and revealed that a longer temporal resolution makes the apparently observed particle dynamics (particle diffusion coe cient, distribution of particle number density) different from the original particle dynamics due to the Brownian motion during the nite temporal resolution (Hanasaki et al 2018). Previous studies have also reported that anisotropic Brownian displacement near the surface by hydrodynamic interaction with the nite temporal resolution can cause a bias error of the measured nanoparticle position (Eichmann & Bevan 2010;Sadr et al 2007;Huang et al 2009;Pouya et al 2015). However, these artifacts owing to the nite temporal resolution have not been su ciently veri ed by experiments.…”
Section: Introductionmentioning
confidence: 99%